حقوق المواطن إتجاه الإدارة الحق في المشاركة في صنع القرار - علاء الدين علايبية (My University, 2025)
Abstract: The principle of the right to participate in decision-making is one of the manifestations of participatory democracy, which aims to involve various actors in society in the management of public affairs and to promote transparency and accountability in state institutions. This right is considered a fundamental component of good governance and contributes to building more democratic and just societies. Citizen participation is characterized by several features: it is popular in nature, dynamic, unlimited, and anchored in legitimacy and democracy. Successive Algerian constitutions have emphasized the necessity of involving citizens in the management of public affairs through various mechanisms within legal frameworks that organize this participation. These mechanisms include: public consultation, administrative investigation, popular oversight, and participatory democracy. Despite the efforts made to strengthen this right, there are still challenges that hinder its full implementation—whether legal, administrative, social, or political. This calls for effective solutions to enhance citizens' participation in the decision-making process. Therefore, strengthening this right requires legal and administrative reforms aimed at facilitating citizen participation in decision-making, promoting transparency and accountability, and empowering civil society to play its role as a mediator between citizens and the administration. This, in turn, will lead to sound governance, transparent administration, and an active citizen who is a partner in development. ............................ الملخص: يعتبر مبدأ الحق في المشاركة في صنع القرار أحد تجليات الديمقراطية التشاركية التي تهدف إلى إشراك مختلف الفاعلين في المجتمع في إدارة الشأن العام وتعزيز الشفافية والمساءلة في مؤسسات الدولة ، يعتبر هذا الحق جزءا أساسيا من الحكومة الرشيدة ويساهم في بناء مجتمعات أكثر ديمقراطية وعدالة، حيث تتميز عملية إسهام المواطن بعدة مميزات أنما ذات طبيعة شعبية ، عملية ديناميكية، ومشاركة المواطن غير محدودة ، والشرعية والديمقراطية. وقد أكدت الدساتير الجزائرية المتعاقبة على ضرورة إشراك المواطنين في إدارة الشأن العام عبر آليات متعددة وذلك ضمن أطر قانونية منظمة لهذه المشاركة تتمثل هذه الآليات في : الإستشارة العمومية والتحقيق الإداري والرقابة الشعبية والديمقراطية التشاركية. رغم الجهود المبذولة لتعزيز هذا الحق لا تزال هناك تحديات تعيق تفعيله بشكل كامل سواء على المستوى القانوني، الإداري، أو الاجتماعي أو السياسي مما يستدعي وضع حلول فعالة لتعزيز مشاركة المواطنين في عملية صنع القرار. وعليه يتطلب تعزيز هذا الحق إصلاحات قانونية وإدارية تهدف الى تسهيل مشاركة المواطنين في عملية صنع القرار وتعزيز الشفافية والمساءلة وتفعيل دور المجتمع المدني كوسيط بين المواطن والإدارة مما ينتج عنه حكم راشد وإدارة شفافة ومواطن نشط وشريك في التنمية. ............................ Abstract: The principle of the right to participate in decision-making is one of the manifestations of participatory democracy, which aims to involve various actors in society in the management of public affairs and to promote transparency and accountability in state institutions. This right is considered a fundamental component of good governance and contributes to building more democratic and just societies. Citizen participation is characterized by several features: it is popular in nature, dynamic, unlimited, and anchored in legitimacy and democracy. Successive Algerian constitutions have emphasized the necessity of involving citizens in the management of public affairs through various mechanisms within legal frameworks that organize this participation. These mechanisms include: public consultation, administrative investigation, popular oversight, and participatory democracy. Despite the efforts made to strengthen this right, there are still challenges that hinder its full implementation—whether legal, administrative, social, or political. This calls for effective solutions to enhance citizens' participation in the decision-making process. Therefore, strengthening this right requires legal and administrative reforms aimed at facilitating citizen participation in decision-making, promoting transparency and accountability, and empowering civil society to play its role as a mediator between citizens and the administration. This, in turn, will lead to sound governance, transparent administration, and an active citizen who is a partner in development.
Keywords: Keywords: decision-making; good governance; citizen; participatory democracy; legal frameworks.; الكلمات المفتاحية: صنع القرار، الحكم الراشد، المواطن، الديمقراطية التشاركية، الأطر القانونية.; Mots-clés : prise de décision; bonne gouvernance; citoyen; démocratie participative; cadres juridiques.